Hubungan Risiko Jatuh Dengan Takut Jatuh Pada Lansia Di Panti Werdha Surabaya - Anastasia Putu Martha Anggaran; Raditya Kurniawan Djoar (Poltekkes Kemenkes Surakarta, 2018)
Abstract Background: Fear of fall will result in reduced equilibrium control and reduced confidence to prevent falls, which will further increase the incidence of falls in the elderly. One effort that can be done to reduce the fear of fall which is the trigger of the incidence of fall is to make preventive efforts that analyze the risk factors, but currently the risk factors associated with fear of falling in the elderly in Indonesia has not been analyzed. The purpose of this study is to analyze the risk relationship falls with the incidence of falling afraid of the elderly living in Panti Werdha Surabaya. Method: The research design was analytic observational with cross sectional approach involving 155 elderly living in Panti Werdha Surabaya. Sampling technique using proportional random sampling method. Existing data were analyzed using Contingency Coefficient Test with significant level of 0.05. Results : The result of the statistical test showed that there was a falling risk relationship with the fear of falling with the correlation value of 0.355 with the significant level of 0.000 (p <0.05), the positive direction indicated by the value of B = 1.425. Conclusion: The risk of falling has a very meaningful relationship with the fear of falling elderly at Panti Werdha Surabaya.